Ethnopolitics of modern Kabardino-Balkaria: genesis and specificity - Aslan Kh. Borov (Кавказология, 2024)
The subject of the research in this article is the historically formed integral “locus” of ethnopolitics – the Kabardino-Balkarian Republic. During the existence of traditional society, the ties between distinct ethnosocial groupings and their social elites within the territory of historical Kabardino-Balkaria were not viewed as interethnic and had no national-political implications. Prerequisites for the emergence of regional ethnopolitics developed during the 19th century, when social and intersocial relations in the Central Caucasus became the subject of regulation by the state. The formation of the Soviet autonomy of Kabardino-Balkaria already acted as a real ethnopolitical process, the subject of which was the coordination of national interests of the Kabardian and Balkar peoples. The illegal act of expulsion from their homeland brought a traumatic beginning to the ethnosocial experience of the Balkar people, which has not been eradicated to this day. Ethnopolitical problems came to the forefront of the social and political life of the multi-ethnic and “two-subject” republic in the conditions of the crisis transition from the Soviet to the modern state and public system in the 1990s and their modern specificity took shape: the interweaving of the processes of socio-political consolidation of the Kabardino-Balkarian Republic and the national consolidation of its “titular” peoples as a deep source of reproduction of ethnopolitics in the social life of the region; an urgent need to confirm the integral national identity of each of the peoples of the republic in the absence of institutional registration of its “two-subject” nature; historical and political discourse as the main field of the “struggle for identity”; the visible asymmetry of the ethno-social structure of the republic and the search for opportunities, conditions and forms of overcoming it as the driving force of Kabardino-Balkarian ethnopolitics at each stage of its actualization.